2021
DOI: 10.1007/s40964-021-00222-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved green and sintered density of alumina parts fabricated by binder jetting and subsequent slurry infiltration

Abstract: Additive Manufacturing (AM) of ceramics is a constantly emerging field of interest both in research and in industry. Binder jetting-based AM of ceramics in particular offers the opportunity to produce large ceramic parts with a high wall thickness at a high throughput. One limitation is that it requires flowable powders, which are generally coarse and thus exhibit only limited sintering activity. The resulting low sintered densities impede the commercial binder jetting-based production of dense oxide ceramics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On the other hand, infiltration has been used to improve sintered parts properties. For example, Vogt et al [49] reached alumina samples with densities above 90% and improved bending strength from 60 to 145 MPa with infiltration of nanometric alumina powder. Also, Maleksaeedi et al [50] showed that infiltration can also improve surface quality, reducing surface roughness (Ra) from 13.2 to 0.9 μm.…”
Section: Binder Jettingmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, infiltration has been used to improve sintered parts properties. For example, Vogt et al [49] reached alumina samples with densities above 90% and improved bending strength from 60 to 145 MPa with infiltration of nanometric alumina powder. Also, Maleksaeedi et al [50] showed that infiltration can also improve surface quality, reducing surface roughness (Ra) from 13.2 to 0.9 μm.…”
Section: Binder Jettingmentioning
confidence: 99%
“…It is usually water-based with some additives for surface tension and viscosity adjustment [41] as isopropyl alcohol [41,45,48], diethyleneglycol [48], polyvinyl alcohol [56], and glycerol [45]. Also, some related works [38,44,49,51] used a commercial aqueous binder (BA005, ExOne). Table II shows the additive manufacturing systems available for binder jetting of ceramics.…”
Section: Binder Jettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Spray-drying granulation was successful in producing a feedstock that could be easily deposited during printing starting from ultrafine feedstocks with limited flowability. Further densification by thermal treatment alone proved to be challenging, however density can be increased by slurry infiltration as observed in literature [22,43]. In this perspective, the preparation of a stable suspension with an optimal rheology is a dual advantage: can be employed for granulation and, on the other hand, for post-processing after sintering.…”
Section: Fundingmentioning
confidence: 99%